PENGARUH PENGETAHUAN MASYARAKAT TENTANG AKAD MUDHARABAH TERHADAP MINAT MENABUNG DI BANK SYARIAH - Restapia, Riska; Nurajizah, Nurajizah (Jurnal Al-fatih Global Mulia, 2022)
Public knowledge about Islamic banking is still small compared to conventional banking. This is not comparable to the people of Indonesia who mostly embrace Islam. Under these conditions, Islamic banking should be more attractive to the Indonesian people, especially the Muslim community. And there are still many people who do not understand Islamic banking, so not many people use Islamic banking services. The purpose of this study was to determine the effect of community knowledge about the Mudharabah contract on the interest in saving at Islamic banks in the Malangnengah village community. This study uses a quantitative approach to data collection methods or questionnaires, interviews and documentation. The population in this study is the community of Malangnengah Village and the sample as research respondents will be taken using the Purposive Sampling technique with the slovin formula, namely 94 people. The data obtained from this study were analyzed using the IBM SPSS 25 program. In this study the authors used the theory of knowledge according to Gazalba (1992) knowledge is what is known or the work of knowing. This knowing work is the result of knowing, realizing, realizing, understanding, and being clever. Knowledge is all owned or the contents of the mind. Mudharabah theory according to Fatwa of the National Syari'ah Council NO: 07/DSN-MUI/IV/2000 concerning Mudharabah Financing (Qiradh) states that Mudharabah is a business cooperation contract between two parties in which the first party (shaibul mal, LKS) provides all the capital , while the second party (mudharib, customer) acts as manager, and business profits are shared between them according to the agreement set forth in the contract. Interest theory According to Muhibbin Syah (2001) interest is a tendency and high excitement or a great desire for something. The results of this study indicate that the community's knowledge variable about mudharabah contracts (X) influences the interest in saving in Islamic banks in the Malangnengah Village community (Y), this can be seen from the results of the t test on the variable community knowledge about mudharabah contracts that it is known that the t_value is 7.744 > from the t_table value of 1.661.